Lacan, Gödel, a ciência e a verdade - Ribeiro, Álvaro Luís dos Santos Gomes (2014)
Jaques Lacan, the thinker who proposes a return to the fundamentals of psychoanalysis in Freud states that the math would face as a privileged way of transmission of knowledge by the science. Although he was a follower of the mathematization of nature as the foundation of modern science, for him this principle does not imply eliminating the subject that produces it. That would be equivalent to saying that there can not be a language, whatever, even the math, that may "erases" the subject assumption in science. In the text The science and the truth we will try to introduce the idea, not so simple, by the way, the truth as the cause. Citing the framework of the causes in Aristotle, Lacan will speak of a homology between the truth as formal cause, in the case of science, and the truth as material cause, on the side of psychoanalysis. Among its aims with this text, he wants to establish that the unconscious of the subject would be none other than the subject of science. The famous incompleteness theorems of logical-mathematical Kurt Gödel enter here as a chapter of this issue. Recognized as true watershed, these theorems have to be remembered as revealing even outside the mathematical environment, and Lacan himself is not indifferent to this. He makes mention of Gödel's name and draws some observations apparently modest support for his own theory. Since some technical sophisticated knowledges awaits the reader who intends understand this supposed corroboration that Gödel provides to psychoanalysis, introduce the student of Lacan in the use he makes of the incompleteness theorems is the objective of this work. In The science and the truth, which fits us to locate the name of Gödel, one must question how seize such an idea without incurring the extrapolation and abuse of mathematical knowledge, almost trivial in this case. Thus, this paper aims to introduce the reader to the reasoning behind the theorems of Gödel, acquaint him about the Lacan’s mathematical claims, and indicate how to proceed using this implicit math in the text The science and the truth.